2006
DOI: 10.1080/10473289.2006.10464459
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ozone-Nitrogen Oxides-Volatile Organic Compound Sensitivity of Cincinnati, Ohio

Abstract: Ambient concentrations of ozone (O 3 ), nitrogen oxides (NO x ), total reactive nitrogen (NO y ), nitric acid (HNO 3 ), and hydrogen peroxide (H 2 O 2 ) were measured during September 2003 at an urban site of Cincinnati, OH. The aim of this study was two-fold: to investigate whether O 3 formation in this population exposure-type site is NO x sensitive or volatile organic compound (VOC) sensitive and to test the practicality of using two combined observational-based methods to identify the sensitivity of O 3 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In both episodes, the isopleths diagrams clearly indicate that O 3 formation in the city is in a VOC-sensitive (or NO xsaturated) regime where O 3 increases with decreasing NO x but decreases with decreasing VOC. Many studies also reported this regime over different cities (especially their central parts) (Milford et al, 1989;Sillman, 1999, and references therein; Kim Oanh and Zhang, 2004;PCD, 2001;Ran et al, 2009;Torres-Jardon and Keener, 2006). Sillman (1999) pointed to a simple rule to suggest the underlying regime of O 3 formation is to consider morning VOC/NO x ratios, <10 as VOC sensitive and >20 as NO x sensitive.…”
Section: Resultsmentioning
confidence: 98%
“…In both episodes, the isopleths diagrams clearly indicate that O 3 formation in the city is in a VOC-sensitive (or NO xsaturated) regime where O 3 increases with decreasing NO x but decreases with decreasing VOC. Many studies also reported this regime over different cities (especially their central parts) (Milford et al, 1989;Sillman, 1999, and references therein; Kim Oanh and Zhang, 2004;PCD, 2001;Ran et al, 2009;Torres-Jardon and Keener, 2006). Sillman (1999) pointed to a simple rule to suggest the underlying regime of O 3 formation is to consider morning VOC/NO x ratios, <10 as VOC sensitive and >20 as NO x sensitive.…”
Section: Resultsmentioning
confidence: 98%
“…As a result, higher weekend ozone values are typically seen in VOC-limited areas, whereas NO x -limited areas tend to have lower ozone concentrations on weekends. However, weekend ozone increases or decreases were observed and modeled in some areas, and in other areas no WD/ WE effect was seen (Blanchard and Tanenbaum, 2006;Blanchard et al, 2008;Graedel et al, 1977;Heuss et al, 2003;Koo et al, 2011;Torres-Jardon and Keener, 2006).…”
Section: Introductionmentioning
confidence: 93%
“…They used model simulations to show that an increase (decrease) in VOCs would result in an increase (decrease) in O3. Hence, we suggest that this effect combined with the reduction in O3 loss due to less titration with NO (Atkinson-Palombo et al, 2006;Torres-Jardon and Keener, 2006;Alghamdi et al, 2014) yields higher O3 concentrations at weekends within these clusters.…”
Section: Seasonal Weekly and Diurnal Profiles Of O3 Concentrationsmentioning
confidence: 74%